2010
DOI: 10.1089/jwh.2010.1937
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Cardiac Rehabilitation Program Tailored for Women on Global Quality of Life: A Randomized Clinical Trial

Abstract: Background: Women with heart disease have adverse psychosocial profiles and poor attendance in cardiac rehabilitation (CR) programs. Few studies examine CR programs tailored for women for improving their quality of life (QOL). Methods: This randomized clinical trial (RCT) compared QOL among women in a traditional CR program with that of women completing a tailored program that included motivational interviewing guided by the Transtheoretical Model (TTM) of behavior change. Two measures of QOL, the Multiple Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Gender‐sensitive educational resources acknowledging private fears about coping with altered functioning, normal sensations and appropriate levels of physical activity could supplement support sessions. This concurs with the findings of Beckie and Beckstead (2010) in their comparison of a traditional cardiac rehabilitation programme with one tailored specifically for women. This randomized control trial identified that the programme tailored to women gave rise to improved quality of life following a cardiac event when compared with the traditional programme.…”
Section: Discussionsupporting
confidence: 89%
“…Gender‐sensitive educational resources acknowledging private fears about coping with altered functioning, normal sensations and appropriate levels of physical activity could supplement support sessions. This concurs with the findings of Beckie and Beckstead (2010) in their comparison of a traditional cardiac rehabilitation programme with one tailored specifically for women. This randomized control trial identified that the programme tailored to women gave rise to improved quality of life following a cardiac event when compared with the traditional programme.…”
Section: Discussionsupporting
confidence: 89%
“…328 Women completing the tailored intervention had significantly improved quality of life and depressive symptoms that were sustained at 6 months compared with those completing traditional CR. 320,329 The tailored intervention also improved 4 dimensions of health: vitality, social functioning, general health, and mental health. 330 Compared with traditional CR, the tailored intervention resulted in significantly greater attendance and higher completion rates.…”
Section: Nonpharmacological Treatment Cardiac Rehabilitation Referralmentioning
confidence: 98%
“…7,22,28,133,138,153 Rehabilitation programmes tailored for women may improve attendance and adherence 154 and may be superior in improvement of quality of life, if compared to traditional rehabilitation programmes. 154 Additional research examining the efficacy of gender-specific and gender-sensitive cardiac rehabilitation programmes, however, remains a major task.…”
Section: Characteristics Of Pa and Exercise Training In Cadmentioning
confidence: 99%